Pendampingan Sertifikasi Halal Self Declare pada Usaha Mikro, Kecil dan Menengah Kecamatan Kedungreja Cilacap: Assistance in Halal Self Declare Certification for Micro, Small and Medium Enterprises Kedungreja Cilacap District - Fathurohim, Fathurohim; Muliyah, Pipit (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Halal Product Process Assistance is a service activity aimed at helping UMKM actors assisted by the Amanu Sejahtera Cooperative in Kedungreja District, Cilacap Regency. The Free Halal Certificate Program (SEHATI) is a free program offered by the Ministry of Religious Affairs of the Republic of Indonesia through BPJPH. This program is one of the government's strategies in accelerating the increase in the number of UMKM actors who have halal certificates. The method in this service activity is PAR (Participatory Action Research), which is a method that involves community participation in halal product process assistance activities in Kedungreja District, Cilacap Regency. Business actors who receive assistance are business actors who join the Amanu Sejahtera Cooperative assisted group with various products such as wet cakes, pastries, chips, various drinks and so on. This assistance is carried out with the aim of training and assisting UMKM actors in filling out the SJPH Manual, creating and filling in components in the SiHalal application, inputting product data in the SiHalal application and verifying and validating products registered through the SEHATI program. The result of this service activity is that UMKM actors assisted by the Amanu Sejahtera Cooperative who are accompanied by get a free halal certificate so that this has added value to the products produced and guaranteed halal products that have been certified halal through the free halal certification program (SEHATI).